Experience of english students education on the departament of infectious diseases - T. E. Onischenko; I. V. Mel’nik; E. V. Ryabokon’ (Zaporožskij Medicinskij Žurnal)
The experience of English speaking students teaching the infectious diseases was summarized, an attempt to establish the recommendation of the organization of the learning process in the specialty was made.